Exploring skin disorders in palliative care: a systematic review - Sara Gonçalves; Maria Martins; Ana Caramelo; Bruno Magalhães; Rita S Matos (Palliative Medicine in Practice)
INTRODUCTION: Skin disorders present significant challenges in palliative care settings, often complicating symptom management and diminishing the quality of life for patients facing life-limiting illnesses. Despite their prevalence and impact, there remains a dearth of comprehensive research synthesizing the landscape of skin disorders within palliative care. METHODS: This systematic review aims to elucidate the spectrum of skin disorders manifested in individuals receiving palliative care, providing a comprehensive understanding essential for effective clinical management and improved patient outcomes. A thorough literature search was conducted across b-on, PubMed, Web of Science, and Scopus, focusing on studies involving human participants aged 18 years or over in palliative care settings. Inclusion criteria encompassed randomized controlled trials, observational studies, and quantitative studies published in peer-reviewed journals, specifically addressing skin disorders as a primary focus or significant aspect of palliative care. RESULTS: From an initial 347 articles, 17 studies met the inclusion criteria. The most common skin disorders identified include pruritus, pressure ulcers, and dermatitis, significantly impacting patients’ physical comfort, emotional well-being, and social interactions. The findings highlight the intricate nature of managing skin disorders in palliative care, necessitating interdisciplinary collaboration and tailored interventions to address the multifaceted needs of this population. CONCLUSIONS: This review underscores the importance of recognizing, assessing, and managing skin disorders to enhance the quality of life of palliative care patients. Future research should focus on developing and implementing targeted strategies to alleviate the burden of skin disorders in this vulnerable group, ultimately improving patient care and outcomes.